Nhu cầu tổ chức và phát triển hoạt động câu lạc bộ bóng chuyền sinh viên: Nghiên cứu trường hợp tại Đại học Kinh tế Thành phố Hồ Chí Minh, Phân hiệu Vĩnh Long - Nguyễn Đại Sơn, Nguyễn Đại Sơn; Nguyễn Quang Sơn, Nguyễn Quang Sơn; Nguyễn Quyết Thắng, Nguyễn Quyết Thắng (Tạp chí Giáo dục, 2026)
In sports club activities, accurately identifying organizational and development needs plays a crucial role, guiding the improvement of club activities towards efficiency and sustainability. Based on this requirement, the study used a combination of document research and questionnaire surveys to identify and analyze the practical needs in the organization and development of the UEH Mekong Student Volleyball Club at the University of Economics Ho Chi Minh City, Vinh Long Campus. The research results identified 15 needs, structured into 5 basic need groups, reflecting relatively comprehensively the organizational, management, and development aspects of the club's activities. These needs were all assessed as highly necessary and were verified through practical surveys conducted among club members. This provides a foundation for building a more effective student volleyball club in the present and lays a solid groundwork for long-term development.